Texas Wildflowers: A Field Guide - Shaffer, Taylor (Journal of the Botanical Research Institute of Texas, 2018)
Campbell & Lynn Loughmiller. Updated by Joe Marcus. 2018. Texas Wildflowers: A Field Guide. (ISBN-13: 978-1-4773-1476-0, pbk). University of Texas Press, 3001 Lake Austin Blvd., 2.200, Stop E4800, Austin, Texas 78703-4206, U.S.A. (Orders: www.utexaspress.com, 1-800-252-3206). $19.95, 512 pp., 320 color photos, 13 drawings, illus. glossary, bibliography, indices, 4.75" × 7.25".